The chemosynthetic biofilm microbiome of deep-sea hydrothermal vents across space and time - Ashley Grosche; Matteo Selci; Francesco Smedile; Donato Giovannelli; Sara Borin; Nadine Le Bris; Costantino Vetriani (Environmental Microbiome)
Abstract Microbial biofilms colonize mineral and biological substrates exposed to fluid circulation at deep-sea hydrothermal vents, providing a biologically active interface along redox boundaries. Since many biofilms at deep-sea vents are associated with invertebrates, microbial distribution and abundance are not only constrained by local fluid geochemistry, but also through host-microbe interactions. This study examined the spatial distribution and diversity of established microbial biofilm communities collected from three distinct biological regimes characteristic of the East Pacific Rise (9°50 N, 104°17 W) vent system, as well as newly established biofilms on experimental microbial colonization devices. Transcripts from 16S rRNA-based amplicon sequencing revealed that Campylobacterota of the Sulfurimonas and Sulfurovum genera dominated newly-formed biofilms across all biological regimes. Statistical analyses using environmental chemistry data from each sampling site suggest that community composition is significantly impacted by biofilm age, temperature and sulfide concentration ranges, and to a lesser extent, locality. Further, metatranscriptomic analyses were used to investigate changes in community gene expression between seafloor and subseafloor biofilms. Our findings revealed differences in the type and abundance of transcripts related to respiratory pathways, carbon fixation and reactive oxygen species (ROS) detoxification. Overall, this study provides a novel conceptual framework for evaluating biofilm structure and function at deep-sea vents by showing a transition from a niche-specific pioneer microbial community in newly-formed biofilms, to a complex population of increased diversity in established biofilms and by identifying key changes in gene expression in taxonomically similar biofilms during the transition from the shallow subseafloor to the seafloor.